Learning from the parallel pathways of Makers to broaden pathways to engineering - Christina Foster; Aubrey Wigner; Micah Lande; Shawn S. Jordan (SpringerOpen, 2018)
Abstract Background Makers are a growing community of STEM-minded people who bridge technical and non-technical backgrounds to imagine, build and fabricate engineering systems. Some have engineering training, some do not. This paper presents a study to explore the educational pathways of adult Makers and how they intersect with engineering. This research is guided by the following research questions: (1) What can we learn about the educational pathways of adult Makers through the lens of constructivist grounded theory? and (2) How do the educational pathways of Makers intersect with engineering? This study relied on qualitative interviews, using artifact elicitation interviews and constructivist critical incident technique interviews, of 42 adult Makers. Results Through inductive analysis of a collection of interviews with Makers, a theme emerged where Makers from different educational backgrounds and with different careers (e.g., art, STEM, business) were making artifacts that had similar purposes. We present two cases of parallel pathways, (1) musical artifacts and (2) large-scale interactive artifacts, to demonstrate the multiple, parallel life pathways that Makers take to making their artifacts and the contextual events and activities that are critical to the direction of these pathways. Conclusions The stories and life pathways of adult learners engaged in Making can offer valuable insight into how we might identify practices that promote the access and success of a larger and more diverse population of students for engineering. Makers are engaged in activities that embody the Engineer of 2020 (e.g., lifelong learning, creativity, and practical ingenuity). By studying Makers, we can consider the multiplicity of pathways into engineering majors and careers.